Ecotheology and Analysis of Christian Education in Overcoming Ecological Problems - Posman Pangihutan; Demsy Jura (GoAcademica Research & Publishing, 2023)
Various environmental problems have become a central focus recently and are expected to increase in the coming years. God's command to Adam and Eve to fill and dominate the earth was not intended to exploit natural resources. As stated in Genesis 1:28,31; 2:15, one of God's purposes for creating humans is to inhabit, rule, and maintain the universe as a sustainable place to live. The method used in this study is a qualitative method with a review of literature on ecotheology and analysis of Christian Religious Education in overcoming ecological problems. The basis for understanding environmental theology (ecotheology) is the awareness that the environmental crisis is not only a secular problem, but also a serious religious problem, because it stems from religious misunderstandings about life. Through environmental theology, a review is carried out on religious understandings in society, especially regarding the position of humans and their responsibilities in relation to the nature that has been inhabited. The environment is a very important subject to pay attention to and of course it must get special attention within the learning and application of Christian Religious Education.